1986
DOI: 10.3171/jns.1986.65.3.0303
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms protruding from the dorsal wall of the internal carotid artery

Abstract: Saccular aneurysms arising at locations other than at arterial divisions are extremely rare. The authors describe eight such aneurysms that protruded from the dorsal wall of the internal carotid artery (ICA) and were unrelated to any arterial junction. Radical surgery was performed in all eight cases. The aneurysms were saccular with a fragile wide or semifusiform neck. Intraoperative rupture occurred in three cases. From this experience, it is emphasized that these unusual protruding aneurysms of the dorsal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
169
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 229 publications
(184 citation statements)
references
References 12 publications
4
169
2
3
Order By: Relevance
“…14 In our study, more than one half of the patients had BBAs on the right side and a history of hypertension, findings that resemble those of others. 13,14,20 Almost all patients had atherosclerotic parent arteries adjacent to the BBAs, but there was no relation to ICA dissection in those in the present study.…”
Section: Clinical Features Of Bbascontrasting
confidence: 37%
See 4 more Smart Citations
“…14 In our study, more than one half of the patients had BBAs on the right side and a history of hypertension, findings that resemble those of others. 13,14,20 Almost all patients had atherosclerotic parent arteries adjacent to the BBAs, but there was no relation to ICA dissection in those in the present study.…”
Section: Clinical Features Of Bbascontrasting
confidence: 37%
“…1 It has also been reported that BBAs occur predominantly on the right side and in females. 13 Frequently, these lesions are associated with hypertension, 13,14,20 arteriosclerosis, 1,6,20 and ICA dissection. 14 In our study, more than one half of the patients had BBAs on the right side and a history of hypertension, findings that resemble those of others.…”
Section: Clinical Features Of Bbasmentioning
confidence: 99%
See 3 more Smart Citations